Radio frequency gradient enhanced diffusion-edited semi-solid state NMR spectroscopy for detailed structural characterization of chemically modified hyaluronic acid hydrogels - Peyman Sakhaii; Bojan Bohorc; Thomas Olpp; Mandy Mohnicke; Joerg Rieke-Zapp; Pradeep K. Dhal (Scientific Reports)
Abstract Applications of functionalized hyaluronic acid (HA) hydrogels for numerous biomedical applications requires their detailed structural characterization. Since these materials are prepared by multistep chemical modifications in the solid phase and not amenable to characterization by standard analytical tools, we employed high-resolution solid-state NMR spectroscopy to gain detailed insights into the structures of the functionalized HA hydrogels. Divinyl sulfone crosslinked HA hydrogels were converted into maleimide-functionalized hydrogels, which were subjected to chemoselective thiol-maleimide reaction using L-cysteine as the protein mimetic thiol reagent. To overcome challenges associated with obtaining high-resolution NMR spectra of crosslinked hydrogels (such as line broadening and overlapping of signals of the hydrogel with those of residual reagents and solvents used during multi-step reaction processes on insoluble polymer matrices), we devised a radio frequency mediated diffusion-edited semi solid-state NMR technique. This technique enabled us to record NMR spectra of hydrogels exclusively by effectively suppressing signals associated with low molecular weight impurities. Thus, it became possible to perform in-depth characterization of these chemically modified HA hydrogels including quantification of reaction outcome for each reaction step.